Climate change and disasters: analysis of the Brazilian regional inequality - Perez, Letícia Palazzi; Rodrigues-Filho, Saulo; Marengo, José Antônio; Santos, Diogo Victor; Mikosz, Lucas (Sustainability in Debate, 2020)
One of the main consequences of climate change in Brazil is the increase in the occurrence of extreme rainfall, which in turn trigger Hydrometeorological disasters; the Brazilian continental dimension, the regional characteristics of biomes and socioeconomic inequality are conditioning factors for the impacts of extreme events in the country.Â This work analyzes Brazil’s socioeconomic and urban infrastructure vulnerability, combined with the regional exposure of the population, based on disasters observed and future scenarios for the occurrence of rainfall extremes. As a result, it points out that climate change impact differently on large Brazilian regions, due to population density and the poor quality of urban infrastructure services.Â